Impact of the electrode proximity on the streamer breakdown and development of pulsed dielectric barrier discharges. (1st March 2022) - Wubs, J R; Höft, H; Kettlitz, M; Becker, M M; Weltmann, K-D
Abstract: The impact of the electrode proximity on the streamer breakdown and development of pulsed-driven dielectric barrier discharges (DBDs) in a single-filament arrangement has been investigated in a gas mixture of 0.1 vol% O2 in N2 at 0.6 bar and 1.0 bar. The gap distance was varied from 0.5 mm to 1.5 mm, and the applied voltage was adapted correspondingly to create comparable breakdown conditions in the gap. The development of the DBDs was recorded by an iCCD and a streak camera system, while fast electrical measurements provided insight into discharge characteristics such as the transferred charge and consumed energy. The results demonstrate that breakdown in a smaller gap is characterised by a slower streamer propagation but a significantly higher acceleration. It can therefore be concluded that the proximity of the cathode has a strong impact on the characteristics of the streamer breakdown. However, after the streamer has crossed the gap, the discharge structure in front of the anode was found to be the same independent of the actual gap distance.